Annotated list of Finnish crane flies (Diptera: Tipulidae, Limoniidae, Pediciidae, Cylindrotomidae) - Salmela, Jukka (Entomologica Fennica, 2012)
A list of Finnish crane fly species is presented (Diptera: Tipuloidea). A total of 331 species are recorded from Finland and presented in a table (Limoniidae 192 spp., Tipulidae 113 spp., Pediciidae 19 spp. and Cylindrotomidae 7 spp.). Twenty-four species are formally reported for the first time from Finland (23 Limoniidae, 1 Tipulidae). Twenty-two species that were previously reported are deleted from the Finnish list (11 Limoniidae, 11 Tipulidae). Locality data, including the occurrence of species within Finnish biogeographical provinces, was available for all but one species. The southern provinces Ta (229 spp.), Ab (226 spp.) and N (203 spp.) are the most species rich; fewer species are found in the northernmost provinces (Le 128, Li 135 spp.). Ten species occur in all 21 provinces whereas 27 species are recorded only from a single province so far. A short review of the history of crane fly research in Finland is provided.